Diastereomeric dinickel(ii) complexes with non-innocent bis(octaazamacrocyclic) ligands: isomerization, spectroelectrochemistry, DFT calculations and use in catalytic oxidation of cyclohexane. Issue 13 (10th March 2022) - Dobrov, Anatolie; Darvasiová, Denisa; Zalibera, Michal; Bučinský, Lukáš; Jelemenská, Ingrid; Rapta, Peter; Shova, Sergiu; Dumitrescu, Dan G.; Andrade, Marta A.; Martins, Luísa M. D. R. S.; Pombeiro, Armando J. L.; Arion, Vladimir B.
Abstract : Dinickel(ii ) complexes with non-innocent bis(octaazamacrocyclic) ligands were isolated as R, S / S, R and R, R / S, S -enantiomers. Abstract : Diastereomeric dinickel(ii ) complexes with bis-octaazamacrocyclic 15-membered ligands [Ni(L 1–3 –L 1–3 )Ni] (4–6) have been prepared by oxidative dehydrogenation of nickel(ii ) complexes NiL 1–3 (1–3) derived from 1, 2- and 1, 3-diketones and S -methylisothiocarbohydrazide. The compounds were characterized by elemental analysis, ESI mass spectrometry, and IR, UV–vis, 1 H NMR, and 13 C NMR spectroscopy. Single crystal X-ray diffraction (SC-XRD) confirmed the isolation of the anti and syn isomers of bis-octaazamacrocyclic dinickel(ii ) complexes 4a and 4s, the syn -configuration of 5s and the anti -configuration of the dinickel(ii ) complex 6a . Dimerization of prochiral nickel(ii ) complexes 1–3 generates two chiral centers at the bridging carbon atoms. The anti -complexes were isolated as meso -isomers (4a and 6a ) and the syn -compounds as racemic mixtures of R, R / S, S -enantiomers (4s and 5s ). The syn-anti isomerization (epimerization) of the isolated complexes in chloroform was disclosed. The isomerization kinetics of 5a was monitored at five different temperatures ranging from 20 °C to 50 °C by 1 H NMR spectroscopy indicating the clean conversion of 5a into 5s . The activation barrier determined from the temperature dependence of the rate constants via the Eyring equation was found to be Δ H ‡ = 114 ± 1 kJ mol −1 with activation entropy Δ S ‡ = 13 ± 3 J K −1 mol −1 . The complexes contain two low-spin nickel(ii ) ions in a square-planar coordination environment. The electrochemical behavior of 4a, 4s, 5s and 6a and the electronic structure of the oxidized species were studied by UV–vis–NIR-spectroelectrochemistry (SEC) and DFT calculations indicating the redox non-innocent behavior of the complexes. The dinickel(ii ) complexes 4a, 4s, 5s and 6a /6s were investigated as catalysts for microwave-assisted solvent-free oxidation of cyclohexane by tert -butyl hydroperoxide to produce a mixture of cyclohexanone and cyclohexanol (KA oil). The best value for KA oil yield (16%) was obtained with a mixture of 6a /6s after 2 h of microwave irradiation at 100 °C.